2023
DOI: 10.13107/jocr.2023.v13.i09.3898
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique of Direct Anterior Approach for Primary Total Hip Arthroplasty Using a Leg Positioning Traction System

Supreet Bajwa

Abstract: Introduction: Through the use of a natural intramuscular and internervous interval, the direct anterior approach (DAA) for total hip arthroplasty (THA) has been suggested to have several advantages over other popular arthroplasty approaches. The usage of DAA for THA has considerably grown in the West in recent years due to the emphasis on tissue preservation and minimally invasive joint replacements. However, due to the long learning curve, literature on this approach originating from India has been inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Hip extension using an operation table has emerged as the principal method for elevation and exposure of the proximal femur and has been extensively studied [ 4 7 ]. Moslemi et al [ 5 ] reported that using a standard table for performing THA via the DAA does not provide better control over leg length than using a traction table, provided preoperative planning is conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Hip extension using an operation table has emerged as the principal method for elevation and exposure of the proximal femur and has been extensively studied [ 4 7 ]. Moslemi et al [ 5 ] reported that using a standard table for performing THA via the DAA does not provide better control over leg length than using a traction table, provided preoperative planning is conducted.…”
Section: Introductionmentioning
confidence: 99%